Análisis de viabilidad en la producción y comercialización de la Guanábana en el Ecuador - Sánchez Ortega, Wilfrido Renee (2023)
This study details what is related to the feasibility analysis in the production and marketing of Soursop in Ecuador. It is estimated that one hectare of Soursop produces 2,000 to 2,500 Kg, that is, about 10 - 15 Kg / plant / year, however, in Ecuador there are no updated figures related to its production. The conclusions determine that soursop requires a high investment of resources to obtain a quality product that must be preserved in harvest and post-harvest practices; To date, a kilo of soursop sells for 1.50 dollars, with an increase of 25 cents more than the previous year; The soursop tree is demanding in Nitrogen, Phosphorus and Potassium mainly, it develops in soils with a slightly acidic pH of 5.5 to 6.5. of 30 days and the application of abundant irrigation is required. It is necessary to carry out all management tasks, from propagation, seedbed, nursery, grafting, sowing, weed, pest and disease control, fertilization, irrigation, pruning, harvest and post-harvest to obtain high production; In Ecuador, nearly 6,000 tons of fresh soursop are produced. The planting conditions on the Ecuadorian coast have an optimal planting density in 6x4 meters for each plant; Marketing is carried out through various distribution channels, this being a producer - exporter; wholesaler – importer; retail; consumer and most people consume it for its multiple benefits as a hydrating fruit, high in potassium and low in sodium, it is digestive, energizing and prevents osteoporosis.